The Golden State in the Civil War Thomas Starr King, the Republican party, and the birth of modern California - Matthews, Glenna (Cambridge University Press, 2012)
This book demonstrates how important California was during the Civil War and provides vivid human detail about the major players in the state. We learn about Confederate sympathizers, patriotic Chinese merchants, fund-raisers for the Union cause in gold-rush towns, among others.